Is Bilingual Education necessary in Icelandic schools? : a response to global needs - Fransheska Echevarria Rojas 1992- (2018)
The active use of English as an international language in the global world has been one of the consequences of globalization. The author of this thesis believes that it is necessary to recognize that English is rapidly expanding as a global language in all nations, and Iceland is one of them. This thesis proposes bilingual education as an educational approach to respond to global trends such as the expansion of English in the Icelandic society, as well as to promote an additional way of learning necessary for students in the twenty-first century. Since Iceland is one of the member countries of UNESCO, this thesis proposes the UNESCO’s four pillars: learning to know, learning to be, learning to do and learning to live together as a guideline to create an effective and qualitative bilingual program to positively influence students’ learning. This thesis is not intended to suggest a radical change in the whole Icelandic educational system, but rather to suggest a different perspective on bilingual education in order to promote new ways of learning in today‘s world. This paper focuses on the following research question: how can bilingual education in Iceland influence student learning in times of globalization? Notkun ensku sem alþjóðlegs tungumáls er ein af afleiðingum hnattvæðingar. Höfundur heldur því fram að það sé nauðsynlegt að gera sér grein fyrir að enska hefur sífellt meira vægi sem tungumál heimsins og þar á meðal á Íslandi. Hér er lögð til tvítyngd kennsla sem menntunarleg nálgun til að bregðast við alþjóðlegri þróun, eins og útbreiðsla ensku í íslensku þjóðfélagi er, sem og að stuðla að nýjum kennsluháttum nauðsynlegum fyrir nemendur á tuttugustu og fyrstu öldinni. Þar sem Ísland er meðlimur að Menningarmálastofnun Sameinuðu þjóðanna (UNESCO), þá er lagt til að Ísland fari eftir fjórum stoðum menntunar sem UNESCO leggur til sem leiðbeiningar um hvernig á að búa til árangursríkt tvítyngt nám sem hefur jákvæð áhrif á hvernig nemendur öðlast og nálgast þekkingu. Stoðirnar fjórar eru: læra að vita, læra að ...